Customers Motivation to Purchase Low Cost Green Car in Indonesia - Sanjaya, Kevin Kynan; Indriani, Mia Tantri Diah (Journal of Business and Management, 2014)
Automotive industry in Indonesia is keep increasing year by year. Many of giant cars manufacturer such as Toyota, Honda, Mitsubishi, and even BMW and Mercedes-Benz have built their own factory in Indonesia. This is indicates the potential of Indonesia automotive industry to have a bright future and promising. Unfortunately, Indonesia is not able to make and develop their own car yet. With this low cost green car program, it is expected that Indonesia could have their own car which built and develop by Indonesian people and also to generate Indonesia automotive industry more evenly. The purpose of this low cost green car program is to provide affordable cars for middle-low class Indonesian people,so it could make them easier to transport. Moreover, with this low cost green car program, it is expected that could develop Indonesia because this car was designed and developed by Indonesian people and must have Indonesian attribute, and also could generates automotive industry more evenly because almost all of the component for this low cost green car is made in Indonesia. The purpose of this research is to get the information the relation between customers knowledge about low cost green car with their motivation to purchase low cost green car in Indonesia. Financially benefit, care to environment health, self-image, social norm and pressure, and interested with new technology is some of the main motivation to purchase low cost green car. This research is using the data which is collected by using questionnaire toÂ the owner of low cost green car in Bandung and Jakarta. The result of this research indicates that the customers motivation to purchase low cost green car is financially benefit. To analyze the data which is gathered by using questionnaire, this research is using descriptive analysis and crosstabs analysis.Keywords: Motivation, Knowledge, Low Cost Green Car